Boredom proneness and inattention in children with and without ADHD: the mediating role of delay aversion - Hsu, Chia-Fen; Chen, Vincent Chin-Hung; Ni, Hsing-Chang; Chueh, Ning; Eastwood, John D. (Frontiers in Psychiatry, 2025)
ObjectiveA high tendency to boredom and delay aversion are commonly observed traits among children and adolescents diagnosed with ADHD. However, the interplay between boredom, delay aversion, and ADHD symptoms remains unclear. It is unknown, for example, whether a predisposition to boredom predicts difficulties in sustaining attention because of susceptibility to delay aversion. This study investigated the potential mediating role of delay aversion in the relationship between boredom and inattentive behaviors in children with and without ADHD.MethodsParent- and self-ratings of boredom proneness, delay aversion, and inattention symptom severity of 93 children with ADHD and 90 typically developing controls (aged 9–16 years) were included in analysis.ResultsBoth parent- and self-ratings showed that children with ADHD had significantly elevated levels of trait boredom, delay aversion, and inattention compared to controls. Trait boredom, delay aversion, and inattention were inter-correlated. The parent-ratings showed that children with a higher level of trait boredom tended to be more inattentive, and this effect was partially explained by the mediating role of delay aversion.ConclusionsOur findings suggest that the relation between boredom and inattention may be at least partially explained by the mediating role of delay aversion in children within and without ADHD.